Real-world shocks and retirement system resiliency - Mitchell, Olivia S. 1953-; Sabelhaus, John; Utkus, Stephen P. (Oxford University Press, 2024)
Labor market shocks and financial stresses are shaping how older workers fare as they head into retirement, as well as how younger workers are preparing financially for their future. These shocks come on top of long-standing concerns surrounding increasing longevity and the adequacy and sustainability of public and private benefit systems. Drawing on exciting new datasets and the perspectives of seasoned as well as new researchers to the field, this volume explores how financial and labor markets, and social as well as private insurance programs, are driving the need for new policy to meet these challenges, along with the need for adaptive changes by households, in an effort to enhance retirement resilience.